Instructors upskilling, reskilling and cross skilling strategies for the organisation of learning and teaching in digital TVET - Tahir, Raihan (Journal of Islamic, Social, Economics and Development, 2025)
Rapid changes and emerging technologies have led to shifting labour market demands and significant transformations in the education and training sector. As traditional industry processes are reshaped by advanced technologies and digitalisation, new occupational profiles are emerging. As a result, young professionals entering the workforce must acquire new competencies to navigate these changes. In response to the rapidly evolving demands of the global workforce, this article addresses the imperative need for skilling, upskilling, and reskilling trainers to effectively prepare the future professionals. The article targets TVET (Technical and Vocational Education and Training) instructors and educational leaders, focusing on strategies to enhance their competencies and adapt to innovative teaching methodologies. Using a combination of the Nominal Group Technique (NGT) and Interpretive Structural Modelling (ISM) approaches, the article systematically gathers insights from 9 TVET experts, each with more than ten years of experiences who identifies and prioritizes strategies for effective TVET instructors’ professional development. The combination of these methods facilitates the collection of expert opinions and the structuring of complex relationships between various factors influencing trainer effectiveness. The outcomes emphasize the adoption of i) technology-enabled learning management. ii) innovative instructional setting/hybrid and iii) technology-mediated session reflection and feedback. The article provides actionable insights into best practices for trainer development, stressing the importance of organisation synchronous and asynchronous sessions. By outlining these prioritized strategies, the article aims to equip trainers with the necessary skills to meet the challenges of tomorrow's workforce and enhance the quality and relevance of vocational education and training.